Psalm’s lyricism in choral works by Mykola Lysenko - Makarenko, Oleksij (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study The awareness of the spiritual music’s significance at the present stage of the musicology science’s development makes it possible to examine the cultural area of the past epochs more fully. Lyrical outlook and spiritual depth typical for the Ukrainian people mentality were most clearly reflected in the music based on liturgical and paraliturgical texts. The scientific discovery in this field becomes more relevant for those relating to the context’s consideration of the musical creativity’s formation, as well as detailed musical analysis of individual liturgical or paraliturgical compositions. Main objective of the study. The purpose of this article is to trace how the texts of the psalms were reflected in the choral works of M. Lysenko. The article analyzes the reasons why Mykola Lysenko drew attention to spiritual creativity and the lyricism of the Book of Psalms. Choral poetry (vocal quartet) "Where do I go from your face" and the choral poem "The Psalm of David" have been analyzed as cases of access to Psalter texts and poetics. In the first case, the composition is created on the original text of the biblical psalm, in the second – on the verse translation of the forty-third psalm by T. Shevchenko. The basic genre features of elegy and psalm, and their correlation among themselves within the choral poem are revealed. Methodology. The study was done using such methods: a comparative method was used for comparative analysis of the primary source’s texts and musical compositions; historical - for the review of M. Lysenko’s creativity and the definition of the psalm’s place in it; analytic – to reveal peculiarities of psalm’s texts reading; semiotic – in identifying the main figurative-content of the sacred works. Results. In the works of N. Lysenko, the interpretation of the texts of the Psalter is not of the traditional approach, but rather a paraliturgical or secular one. He tries to reveal the ideas of the psalms in artistic, aesthetically-generalized way: an emotional romantic understanding of God Who is everywhere, His grace, and national idea. Consequently, the psalm’s lyricism in M. Lysenko’s choral work appears indirectly, and has an elegiacal genre interpretation.